NKG2D Ligands in Tumor Immunity: Two Sides of a Coin - Zhang, Jinyu; Basher, Fahmin; Wu, Jennifer D. (Frontiers in Immunology, 2015)
The activating/co-stimulatory receptor NKG2D (natural-killer group 2, member D) is expressed on the surface of all human NK, NKT, CD8+ T and subsets of γδ+ T cells. The significance of NKG2D function in tumor immunity has been well demonstrated in experimental animal models. However, the role of human NKG2D ligands in regulating tumor immunity and cancer prognosis had been controversial in the literature. In this review, we summarize the latest advancement, discuss the controversies, and present evidence that membrane-bound and soluble NKG2D ligands oppositely regulate tumor immunity. We also discuss new perspectives of targeting NKG2D ligands for cancer immunotherapy.